Vakinn, the official quality and environmental system within Icelandic tourism - Edda Björg Bjarnadóttir 1989- (2016)
This thesis, analyses Vakinn certified companies to identify the motives for seeking Vakinn, the official quality and environmental system within Icelandic tourism. It also analyses the reported benefits of implementing Vakinn and furthermore, analyses the use of various quality tools, which measure quality and are implemented within companies. Furthermore, the study compares these factors between sectors within the tourism industry and between companies, based on their last year’s turnover. The motives were divided into internal and external reasons. Participants were divided into groups based on the scoring of those reasons. Participants sought Vakinn for internal reasons, external reasons and a combination of these two reasons. The results indicate that companies which seek Vakinn for internal reasons, report higher levels of benefits, but do not use quality tools more frequently, than those that seek Vakinn for external reasons. Companies that seek the certificate for external reasons use quality tools to a greater extent than those that seek Vakinn for internal reasons. The difference between sectors of industry and between companies was insignificant. Restaurants and cafés report the highest level of benefits and use quality tools more frequently than other sectors. Those who checked the option “do not want to answer” of the question regarding sector of industry, scored lowest in benefits, but highest in use of quality tools. The main limitation of this study was the small sample size due to the limited population size; only 51 companies were Vakinn certified when this study was conducted. Keywords: Quality certification, Internal benefits, External benefits, Quality tools, Iceland, Tourism Industry, Vakinn